199k views
4 votes
Which of the following expressions is equivalent to (y-3)^4 ?

Which of the following expressions is equivalent to (y-3)^4 ?-example-1
User Sudeep
by
5.3k points

1 Answer

1 vote

ANSWER :

The answer is A. y^4 - 12y^3 + 54y^2 - 108y + 81

EXPLANATION :

From the problem, we have the expression :


(y-3)^4

we can write it as :


(y-3)^4=[(y-3)^2]^2

Perform the first power to the 2nd using :


(a^2\pm b^2)=a^2\pm2ab+b^2


[(y-3)^2]^2=(y^2-6y+9)^2

Next is to perform the next square :


(y^2-6y+9)^2=(y^2-6y+9)(y^2-6y+9)

We can distribute each term of the first parenthesis to the second parenthesis as :


(a+b+c)(a+b+c)=a(a+b+c)+b(a+b+c)+c(a+b+c)

Then :


\begin{gathered} (y^2-6y+9)(y^2-6y+9) \\ =y^2(y^2-6y+9)-6y(y^2-6y+9)+9(y^2-6y+9) \\ \text{ Then simplify :} \\ =(y^4-6y^3+9y^2)-(6y^3-36y^2+54y)+(9y^2-54y+81) \\ \text{ Combine like terms :} \\ =y^4-6y^3-6y^3+9y^2+36y^2+9y^2-54y-54y+81 \\ =y^4-12y^3+54y^2-108y+81 \end{gathered}

User Neghez
by
4.8k points